Delftia acidovorans Infections in Immunocompetent and Immunocompromised Hosts: A Case Report and Systematic Literature Review - Scaglione, Vincenzo; Stefanelli, Lucia Federica; Mazzitelli, Maria; Cattarin, Leda; De Giorgi, Loreta; Naso, Elena; Maraolo, Alberto Enrico; Cattelan, Annamaria; Nalesso, Federico (Antibiotics (Basel), 2025)
Delftia acidovorans (D. acidovorans) is a non-fermentative, aerobic, Gram-negative bacillus typically found in environmental sources such as soil and water. Although considered an opportunistic pathogen, it has been implicated in both immunocompromised and immunocompetent individuals. This study presents a case of persistent cathether-related bacteraemia in a 61-year-old haemodialysis patient and offers a systematic literature review of similar cases. The patient, affected by end-stage kidney disease and dependent on a central venous catheter (CVC), presented with septic shock. Blood cultures confirmed D. acidovorans, resistant to aminoglycosides but sensitive to cephalosporins, piperacillin/tazobactam, and fluoroquinolones. Despite appropriate antibiotic therapy, bacteraemia persisted, prompting the use of taurolidine lock therapy when catheter removal was initially unfeasible. Blood cultures cleared after nine days, and the catheter was later replaced. A systematic review following PRISMA guidelines identified 21 additional cases of D. acidovorans bacteraemia. Most (76.2%) occurred in immunocompromised patients, particularly those with malignancies, chronic haemodialysis, or indwelling devices. Infections in immunocompetent individuals were typically associated with intravenous drug use or environmental exposure. Mortality was approximately 19%. Aminoglycoside resistance was consistent across most cases, while susceptibility to piperacillin/tazobactam, cephalosporins, and carbapenems was generally preserved. Given its resistance profile and ability to form biofilms, D. acidovorans poses a management challenge, particularly in catheter-associated infections. Rapid identification and targeted antimicrobial therapy are crucial. Adjunctive measures such as taurolidine lock therapy can be beneficial when device removal is not immediately possible.